Impact of Needle Design and Suture Gauge on Tissue Tearing During Skin Suturing: A Comparative Analysis - Potter, Christian T; Maloney, McKenzie E; Riopelle, Alexandria M; Fudem, Gary M; Schanbacher, Carl F (Dermatologic surgery, 2025)
Surgeons face numerous choices in selecting sutures for skin closure, with potential adverse effects such as tissue tearing. To investigate the influence of needle design and suture gauge on tissue tearing during suturing procedures. The authors tested the tear-through force in Newtons for 3 needle types and 3 suture gauges using an artificial skin model and a professional-grade tensiometer. Suture material was secured into the skin model, and force was applied to the suture at a constant rate, resulting in tearing. Force-displacement and force-time curves were generated. Evaluation included conventional cutting (PC-3), reverse cutting (PS-3), and taper point (BB) needles with a 5-0 polypropylene suture. In addition, nylon sutures with a reverse cutting needle (PS-2) were tested at 3 suture gauges (5-0, 4-0, 3-0). The mean tear-through forces for PC-3, PS-3, and BB were 3.26 N, 3.75 N, and 4.07 N, respectively. For the 5-0, 4-0, and 3-0 nylon sutures, the mean tear-through forces were 3.44 N, 3.81 N, and 4.04 N, respectively. Statistical analysis revealed a significant impact of suture gauge size ( p < .001) and needle geometry ( p < .001) on tear-through force. Larger suture diameter and taper needles minimize tissue tearing.